The Politicization of Radicalism Issues and Its Impact on Social Harmony in Multicultural Societies: An Analysis of Interfaith Student Perspectives in Kendari - Taufani Taufani; Zainal; Hidayah Rahman; Tita Juwita Nur (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Radicalism has become one of the most contested sociopolitical issues in Indonesia, a nation characterized by profound religious, ethnic, and cultural diversity. Objectives: This qualitative study investigates how radicalism discourse is politicized in multicultural campus environments and the consequences of such politicization for interfaith social harmony in Kendari, Southeast Sulawesi. Method: Drawing on in-depth interviews with sixteen student informants representing eight campus-based religious and sociopolitical organizations — KAMMI, HMI Dipo, HMI MPO, IMM, PMKRI, Hindu Student Organization, GMKI, and Gema Pembebasan — the study finds that radicalism narratives are frequently weaponized as electoral instruments to discredit political opponents, thereby reinforcing identity-based polarization. Results: Informants consistently observed that the misuse of the